Analisis Hukum Kedudukan Lembaga Negara Berdasarkan UUD 1945 Dalam Sistem Ketatanegaraan Indonesia - Rohmatul Jannah; Dyah Hayu; Ersy Aulia; Lois Salwa; Fathan Akbar; Kuswan Hadji (Lembaga Pengembangan Kinerja Dosen, 2024)
Indonesia is a unitary state that places law as the highest basis that regulates all state life. The consequence of Indonesia as a rule of law state is that all government institutions in the formation and exercise of authority must also be based on applicable legal regulations so that they are not based on mere power. The rule of law also regulates how state institutions carry out their duties as an attribute of state completeness. State institutions domiciled in Indonesia, or in this case the distribution of state power, have a structured hierarchy. To be able to carry out a national life in Indonesia, the constitutional system is regulated by a system of checks and balances between state institutions. Using a normative juridical approach, with analytical descriptions and literature studies, it was discovered how the relationships between state institutions in the Indonesian constitutional system are found. The position of state institutions in this constitutional system is not only divided but also limited by law